Endoscopic resections in urology - Gayol Collete, Mario; Batista, Néstor; Grunwald, Izso; García Guido, Luis; Sosa Pandolfo, Pedro; Darcht, Alejandro (Cirugía del Uruguay, 1983)
History and experience of four years about Encospical Transuretral Surgery (ETS) and its present situation in our country, are related. Conditions and irnperative needs in order to assure such proceedings and the advantages they have on the patient and its social pattern, are analized.